Numerical Analysis of Convective Transport of Fly Ash-Water Slurry through a Horizontal Pipe. (June 2015) - Nayak, Bibhuti Bhusan; Gupta, Satish Kumar; Chatterjee, Dipankar; Mullick, Amar Nath
The thermal transport of solid-liquid suspension under turbulent flow condition is not well understood because of the complex interaction between the solid particles and the turbulent carrier fluid. The solid particles may enhance or suppress the rate of heat transfer and turbulence depending on their size and concentration. In the present paper, a three-dimensional numerical simulation is carried out in order to study the pressure drop and heat transfer characteristics of a liquid-solid slurry flow in a horizontal pipe. The simulation is performed by using the algebraic slip mixture (ASM) model which is a part of the finite-volume based CFD software Ansys Fluent. The turbulence is handled by the RNG k – ε model. A hexagonal shape and cooper type non-uniform three-dimensional grid is created to discretize the computational domain. Spherical fly ash particles, with mass median diameter of 13mm for an average flow velocity ranging from 1–5 m/s and particle concentrations within 0–40% by volume for each velocity, are considered as the dispersed phase. The results illustrate that higher particle concentration in the flow causes an increase in the heat transfer and pressure drop. Moreover, both heat transfer and pressure drop are seen to show a positive dependence on the mean velocity of the flow.